Ophthalmic contraindications to sports - SzalińskI, Marek; Pupka, Artur; Misiuk-Hojło, Marta (Klinika Oczna / Acta Ophthalmologica Polonica, 2021)
Sports activity in ophthalmic patients is an insufficiently understood and developed topic, which is reflected in the small number of publications on this subject and the lack of precise guidelines available both in the materials of scientific societies and in textbooks used by doctors during preparation for the specialization exam. The number of amateur sports people has been growing recently and questions about the possibility of undertaking physical effort after surgery are common among ophthalmic patients. The authors of the article review the available sources of knowledge to bring closer the issues indicated in the title of the work. Conditions after glaucoma and retinal detachment, refractive operations and other inoperable conditions such as central serous retinopathy and eye surface diseases are discussed.